A Framework for Integrating Gamification Mechanics and Dynamics to Authentic Learning Environment (Ale) in Non-Game Context - Nafisah Syed Muhammad, Sharifah; Idrus, Rosnah; Lee Abdullah, Nasuha; Keikhosrokiani, Pantea (International Journal of Engineering and Technology, 2018)
One of the most important factors for students’ development and achievement is their engagement level with the learning activities.  However, some students are lacking in essential 21st century skills that are important for their working life and daily activities.  The essential skills are associated with high level thinking skill.  Authentic learning environments promote the environment for high-level thinking skills.  In order to engage students and confront their motivational problems, gamification approach is integrated into the authentic learning environment.  Gamification uses game mechanics and dynamics in a non-game context to motivate, engage and reward user for completing tasks.  This paper proposes a conceptual framework and for gamified learning environment according to the guideline and characteristics of authentic learning and integrates it with the relevant gamification mechanics and dynamics embedded into an application prototype.  The prototype, named Time+ (Time Plus), is developed with an example topic of Time Management as the non-game context of higher order thinking skills.  The aim of this study is to help students improve their engagement positively and enrich the educational experiences for the current millennial students by adapting the gamification concepts in a non-game context.  Furthermore, it can also encourage students to learn while engaging with the gamified learning environment and enhance the modern teaching and learning methods.
Keywords: Gamification in Education; Mechanics and Dynamics; Student Motivation; Student Engagement; Authentic Learning Environment